Portuguese cork industry is Vit/Enol Seminar series topic, Sept. 25 - Uribes, Tom::::::::: (2013)
Fresno State student Doris Michue, chosen for the 2013 ACI Cork Award of Excellence, will speak at the Viticulture and Enology Seminar Series.